The Effect of Corporate Governance for Financial Performance in LQ45 Companies That Will Be Listed in The Indonesia Stock Exchange From 2017 - 2021 - Rahmi Khairani; Dina Patrisia (Universitas Negeri Padang, 2023)
Company performance ratings are used as a measure of success in decision-making management, as success in achieving company goals is management's output. The purpose of this research is to ascertain how management with ownership, the board of commissioners, and independent commissioners affect LQ45 companies' financial performance on the IDX. The method for gathering the data is to use annual financial report data from LQ45 companies that are listed on the Indonesia Stock Exchange and can be accessed through the IDX website for the years 2017 to 2021. Nine companies meet the criteria for the research sample. The findings indicate that managerial ownership has a significant impact on ROA, while independent commissioners have no significant impact on ROA in LQ45 companies listed on the Indonesia Stock Exchange and the number of commissioners has a significant impact on ROA. However, ROA in LQ45 companies listed on the Indonesia Stock Exchange between 2017 and 2021 is unaffected by the combined number of commissioners and independent commissioners.